Metabolic profiling of different wild and cultivated Allium species based on high‐resolution mass spectrometry, high‐performance liquid chromatography‐photodiode array detector, and color analysis. (5th May 2020) - Maccelli, Alessandro; Cesa, Stefania; Cairone, Francesco; Secci, Daniela; Menghini, Luigi; Chiavarino, Barbara; Fornarini, Simonetta; Crestoni, Maria Elisa; Locatelli, Marcello
Abstract: Many plants of the genus Allium are widely cultivated and consumed for their nutraceutical and health‐enhancing bioactive components effective in many metabolic and infectious diseases. In particular, Allium sativum L. (garlic), the most economically important Allium species, is known to present volatile, comparatively polar sulfur‐containing compounds responsible for both the typical garlic aroma and antimicrobial property. More recently, the (moderately) polar portion of garlic metabolome, rich of polyphenols and amino acids, is gaining increasing interest as a source of antioxidants and primary nutrients. In this study, we have explored the chemical diversity of eight different hydroalcoholic extracts obtained by microwave‐assisted extraction of white and red crop A. sativum and wild Allium triquetrum, Allium roseum, and Allium ampeloprasum, all originating from the Mediterranean Basin. The aim is to appraise their potential dietetic and healing value through an in‐depth chemical characterization and contribute to preserve and exploit natural resources. The multimethodological method applied here is based on an untargeted metabolic profiling by means of high‐resolution electrospray ionization Fourier‐transform ion cyclotron resonance (ESI FT‐ICR) mass spectrometry. More than 850 by ESI(+) and 450 by ESI(−) putative metabolites have been annotated covering all main classes of primary and secondary metabolites, including amino acids, alkaloids, organic and fatty acids, nucleotides, vitamins, organosulfur compounds, and flavonoids. The pigment and polyphenol components have been separated and quantified by a targeted chromatographic high‐performance liquid chromatography‐photodiode array detector (HPLC‐PDA) and CIEL*a*b* colorimetric assay, showing characteristic yellow and red components in each extract, related to a different milieu of anthocyanins and flavonoids as assigned by high‐resolution mass spectrometry (MS).